Conserving biodiversity in agriculture-dominated landscapes: Loss of natural habitat drives lepidopteran declines at multiple spatial scales - Feswick, April Amanda Melissa (University of Ottawa (Canada), 2006)
The expansion of agriculture throughout the world has precipitated serious biodiversity losses. Countries with relatively extensive natural habitats, such as Canada, continue to intensify agricultural land uses, threatening to expand the scope of the present mass extinction. This thesis tests likely mechanisms of butterfly species decline in agricultural landscapes of varying intensities in the most biologically diverse region of Canada. I measured site variables such as the richness of plants suitable for larval development, patch area and shape index, and landscape variables such as heterogeneity and land-cover within buffers that varied in size from 100m to 1000m. Several rare species were not present in the agricultural sites, whereas a few species typically associated with disturbed habitat were present and abundant among most study sites. I found that agricultural intensification acts across landscapes to reduce butterfly species richness by reducing the proportion of natural habitat available. This effect was especially pronounced at 100m to 200m distances, suggesting a threshold effect beyond which the proportion of natural land is less critical to butterfly biodiversity. Within-site factors, such as plant species richness and habitat area were not affected by agricultural intensity, nor did they affect butterfly species richness and abundance. These results suggest that the mechanism linking butterfly species decline to agriculture, at least for butterflies in this region, is the loss of small habitat remnants.
Keywords: Biology, Ecology.